Photogrammetric documentation of Czechoslovak border fortifications at Hlučín-Darkovičky - Kapica, Roman; Vrublová, Dana; Michalusová, Markéta (Geodesy and Cartography, 2013)
The Institute of Geodesy and Mine Surveying of the Technical University Ostrava makes photogrammetric surveying of major built objects in the Moravian-Silesian region. The focus of the present study is on special monuments that form integral parts of regional history and make outstanding landmarks. Terrestrial photogrammetry was used as the surveying methods used. The primary goal of photogrammetric surveying is to identify geometric shapes and to create visualisations of objects. Photogrammetric surveying provides valuable documentary data for uses in the areas of the history of architecture and technical research as well as for renovations and advertising campaigns. Our 3D models were created by using terrestrial digital photogrammetry.